Editorial Introduction - Gordon Wells (Networks: An Online Journal for Teacher Research, 2005)
As the result of a number of problems, this issue has been a long time in coming. But, as usual, it contains a collection of stimulating articles that each, in its way, reports an attempt to bring about improvement in the quality of learning in a particular setting. Providing a common thread across these articles is the issue of motivation, which is both a prerequisite for, and an outcome of, the kinds of learning that aim for understanding and are the basis for effective and responsible action.